Model Hidrologi Untuk Analisis Pengaruh Perubahan Tata Guna Lahan Terhadap Potensi Ketersediaan Air Di Daerah Aliran Sungai (DAS) Siak - Muhammad Iqbal; Sigit Sutikno; Ari Sandhyavitri (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2015)
Significant shift in the land use within Siak watershed (DAS Siak) affects to groundwater reserves. This also affected to fluctuation of the river flows. Therefore to develop a comprehensive watershed management strategies, it is required a hydrological model which is in capable to represent the hydrological cycle of the watershed. Hydrological model may use SWAT application software package. The SWAT simulations performed various scenarios for land use changes in the period of 2002, 2007, and 2012. Based on this research study, the optimal determination coefficient (R2) of SWAT output models were = 0.59, with Nash Suflicfe Efficiency (NSE) was 0.58. The determination coefficient for validation models was 0.55 and NSE was 0.48. These results have satisfied the reserach objectives as the findings coefficient were > R2 min 0.4, and >NSE 0.35. The level of ground water reserves was calculated by comparing the ratio of Qmaximum and Qminimum during the period of 2002 to 2012. It was revealed that the ratio of ground water reserves were as the following order 10,725 (2002), 6,834 (2007) and 12,951 (2012) respectively. Should the ratio value Qmaxsimum / Qminimum was bigger, the more critical ground water reserved will be. Hence, the fundamental changes in land use is Siak watershed affected to suppress the ground wateer reserve to the critical level.Keywords: Land use change, SWAT model, ground water reserve.